2023
DOI: 10.1093/inthealth/ihad010
|View full text |Cite
|
Sign up to set email alerts
|

Online interviews for qualitative health research in Africa: a scoping review

Abstract: Online interviews can be powerful tools in global health research. In this article, we review the literature on the use of and challenges associated with online interviews in health research in Africa and make recommendations for future online qualitative studies. The scoping review methodology was used. We searched on Medline and Embase in March 2022 for qualitative articles that used internet-based interviews as a data collection method. Following full-text reviews, we included nine articles. We found that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Participants had the option to choose between online interviews conducted via the GoToMeeting 10.19.0® Software or face-to-face. Peasgood et al (2023) found no significant differences in understanding questions, engagement or concentration between face-to-face and online interviews [ 44 , 45 ]. Digital assessments were familiar to participants due to pandemic-related adjustments within the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Participants had the option to choose between online interviews conducted via the GoToMeeting 10.19.0® Software or face-to-face. Peasgood et al (2023) found no significant differences in understanding questions, engagement or concentration between face-to-face and online interviews [ 44 , 45 ]. Digital assessments were familiar to participants due to pandemic-related adjustments within the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Recent outbreaks of diseases like Ebola, Covid-19, and monkeypox have exposed how stigma continues to hinder healthcare access, especially for vulnerable groups such as men who have sex with men 15 . In South Africa, a significant percentage of HIV-positive individuals experienced high levels of HIV-related stigmatizing attitudes, while stigma related to type 2 diabetes ranged from 49.6% in Ghana to 70% in Ethiopia 16 , 17 . Stigma was reported by Ebola survivors and their communities in DR Congo, Guinea, and Liberia 18 .…”
Section: Current Situation Of Stigma and Infectious Diseases In Africamentioning
confidence: 99%
“…The complexity of the etiology of diabetes and the diversity of symptoms deserve our consideration. Diabetic stigma has attracted the attention of scholars [ 5 ]. With the aging of populations worldwide, the incidence and prevalence of chronic diseases and the economic burden on healthcare providers remain very challenging [ 6 ].…”
Section: Introductionmentioning
confidence: 99%